PENDAMPINGAN KEGIATAN PENDIRIAN KIOS SEMBAKO UNTUK MENAMBAH PENDAPATAN PKK RT 01/RW 06 KELURAHAN GADING KASRI - Dewi Nurjannah; Sri Nastiti Andarini (Bajang Institute, 2025)
The Family Welfare Movement (PKK) group in RT 01/RW 06, Gading Kasri sub-district, which is a partner in this community service, operates a cooperative. Because it is not yet a legal entity, it is actually still a pre-cooperative. All members have shares/principal savings, mandatory savings, and voluntary savings/savings. The